MODELING MEDIUM-DUTY VEHICLE PERFORMANCE WITH HYBRID DIFFERENTIAL-BASED TRANSMISSION GT-POWER SIMULATION & EXPERIMENTAL ANALYSIS - Asrul Syaharani Yusof (Tesis, 2024)
Medium-heavy load vehicles move from a static position at a slow pace with gradual acceleration. Thus, for mobility at rough inclined terrain or achieving higher speed in less time require extra torque from the transmission. In this situation, a power split device (PSD) is needed to add extra power from another source, such as electric motor.Therefore, a differential gear-based power split device (DPSD) can instead be employed. A DPSD was fabricated for the experiment. The simulation model was developed using GT-Power software.